Model of european men's handball in the year 2000 - Skarbalius, A. (Education. Physical training. Sport, 2000)
The individual competitive activities of separate players of a handball team as well as competitive activities of the team as a whole are extremely multiform. Thus, for instance, over 300 indices could be used to characterize the actions of the team in defence. The variety of indices characterizing the competitive activities in handball being so great it is of particular importance that the main, essential indices enabling one to objectively estimate the sports preparedness of the team and its correspondence to the standard of elite teams be established. The national teams of European countries, participants of the teams of European countries, participants of the championship of the continent are representatives of the world handball elite at the same time. With an aim to forecast the tendencies in the game of handball it is obligatory that the parametres of competitive activities and components of preparedness of elite national teams be established. The aim of the study was to establish the preparedness and playing pecularities of handball national teams at the European men's handball championship of the year 2000. On the basis of the official documents drawn by the European Handball Federation at the 4th Europeran Men`s handball championship, methods of the mathematical statistics (arithmetical mean, standard deviation, significance of mean differences according to Student`s "t" criterion) the competitive activities of separate national teams have been systematized, arithmetical means of indices have been established and a comparative analysis has been carried out. Indices (n=38 matches) of national teams of 12 European countries (n=169 participants) have been estimated. Indices of height, body mass, age and competitive experience (the number of the matches played as a member of the national team and the number of the goals scored) of handball players and their competitive activities (the average number of the goals scored per match, the efficiency of attacks and types of attacks, the percentage structure of throws and their efficiency, the efficiency of the playing of goalkeepers, positive and negative actions) were taken into account. In comparison with the previous European championship an improvement in the indices of height, body mass, age and competitive experience has been found out. The indices of competitive activities correspond to the standard of competitive activities demonstrated at the 3rd European championship of the year 1998 and the world handball championship held in 1999. The national team of Sweden, champion of Europe, excells its rivals in competitive experience and efficient playing of goalkeepers. National teams possessing greater competitive experience became prize winners of the championship.